A forensic identification case and DPid - can it be a useful tool? - Cristhiane Leão de QUEIROZ; Ellen Marie BOSTOCK; Carlos Ferreira SANTOS; Marco Aurélio GUIMARÃES; Ricardo Henrique Alves da SILVA
Abstract Objective The aim of this study was to show DPid as an important tool of potential application to solve cases with dental prosthesis, such as the forensic case reported, in which a skull, denture and dental records were received for analysis. Material and Methods Human identification is still challenging in various circumstances and Dental Prosthetics Identification (DPid) stores the patient's name and prosthesis information and provides access through an embedded code in dental prosthesis or an identification card. All of this information is digitally stored on servers accessible only by dentists, laboratory technicians and patients with their own level of secure access. DPid provides a complete single-source list of all dental prosthesis features (materials and components) under complete and secure documentation used for clinical follow-up and for human identification. Results and Conclusion If DPid tool was present in this forensic case, it could have been solved without requirement of DNA exam, which confirmed the dental comparison of antemortem and postmortem records, and concluded the case as a positive identification.